The Safety and Immunogenicity of an Interleukin-12–Enhanced Multiantigen DNA Vaccine Delivered by Electroporation for the Treatment of HIV-1 Infection. (1st February 2016) - Jacobson, Jeffrey M.; Zheng, Lu; Wilson, Cara C.; Tebas, Pablo; Matining, Roy M.; Egan, Michael A.; Eldridge, John; Landay, Alan L.; Clifford, David B.; Luetkemeyer, Anne F.; Tiu, Jennifer; Martinez, Ana L.; et al.
Abstract : Background: Therapeutic vaccination is being studied in eradication and "functional cure" strategies for HIV-1. The Profectus Biosciences multiantigen (MAG) HIV-1 DNA vaccine encodes HIV-1 Gag/Pol, Nef/Tat/Vif, and Envelope, and interleukin-12 (IL-12) and is delivered by electroporation combined with intramuscular injection (IM-EP). Methods: Sixty-two HIV-1–infected patients on antiretroviral therapy (plasma HIV-1 RNA levels ⩽200 copies/mL; CD4 + T-cell counts ≥500 cells/mm 3 ) were randomly allocated 5:1 to receive vaccine or placebo. At weeks 0, 4, and 12, 4 consecutive cohorts received 3000 μg HIV MAG pDNA with 0, 50, 250, or 1000 μg of IL-12 pDNA by IM-EP. A fifth cohort received HIV MAG pDNA and 1000 μg of IL-12 pDNA by standard IM injection. Results: CD4 + T cells expressing IL-2 in response to Gag and Pol and interferon-γ responses to Gag, Pol, and Env increased from baseline to week 14 in the low-dose (50-μg) IL-12 arm vs. placebo ( P < 0.05; intracellular cytokine staining). The total increase in the IL-2–expressing CD4 + T-cell responses to any antigen was also higher in the low-dose IL-12 arm vs. placebo ( P = 0.04). Cytokine responses by CD8 T cells to HIV antigens were not increased in any vaccine arm relative to placebo. Conclusions: HIV-1 MAG/low-dose IL-12 DNA vaccine delivered by IM-EP augmented CD4 + but not CD8 + T-cell responses to multiple HIV-1 antigens. Abstract : Supplemental Digital Content is Available in the Text.